Endovascular treatment of a right pulmonary sequestration supplied by an aneurysmal aberrant artery originating from the abdominal aorta - Marine,Leopoldo (2022)
Abstract Endovascular embolization of arteries feeding pulmonary sequestrations is a growing therapeutic option. A 51-year-old woman with chest pain and hemoptysis was admitted. During hospitalization she presented 150 mL hemoptysis, hypotension, and hematocrit fell to 23.3%. Contrast-enhanced computed tomography confirmed a pulmonary sequestration irrigated by an aneurysmal artery from the abdominal aorta. The patient underwent endovascular coil embolization of the artery feeding the aneurysm and an Amplatzer device was deployed in the proximal third of the sequestration artery. Subsequent contrast-enhanced computed tomography confirmed complete thrombosis of the aberrant artery feeding the aneurysm and absence of irrigation of the pulmonary sequestration. At 56 months follow-up the patient remains asymptomatic, tomography showed involution of the sequestration and complete thrombosis of the aberrant artery. The challenges presented by the different treatment alternatives are discussed.